2014
DOI: 10.1111/ctr.12490
|View full text |Cite
|
Sign up to set email alerts
|

Skin cancer evaluation in transplant patients: a physician opinion survey with recommendations

Abstract: The dermatologic evidence for regular skin cancer screening in transplant patients needs dissemination to our transplant colleagues. This is a significant practice gap which can be appropriately closed by integrating dermatologists into the transplant team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 79 publications
1
15
0
1
Order By: Relevance
“…In a population of SOTRs, Lloyd et al 16 found that 49% of patients with metastatic cutaneous malignancies died from their disease. Yet, 72% of these deceased SOTRs were seen by physicians who seldom referred patients for dermatologic screening 16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a population of SOTRs, Lloyd et al 16 found that 49% of patients with metastatic cutaneous malignancies died from their disease. Yet, 72% of these deceased SOTRs were seen by physicians who seldom referred patients for dermatologic screening 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In a population of SOTRs, Lloyd et al 16 found that 49% of patients with metastatic cutaneous malignancies died from their disease. Yet, 72% of these deceased SOTRs were seen by physicians who seldom referred patients for dermatologic screening 16 . Additionally, Ong et al 25 found that 27% of heart transplant recipients died due to untreated skin cancer within four years of their transplant date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A primer prevenció részeként fontos lenne már a transzplantáció előtt a betegek egyéni rizikófaktorainak felmérése, bőrük vizsgálata, figyelmük felhívása és oktatásuk a megfelelő fényvédelmi módszerek alkalmazására és a havonkénti rendszeres önvizsgálatra [17,22,28,29]. Az egyéni rizikófaktoroktól függően a transzplantált betegek 3, 6, 12 havonkénti bőrgyógyászati vizsgála-ta lenne indokolt [25,29].…”
Section: Megbeszélésunclassified
“…In the literature, the primary barriers to skin cancer screening include access to dermatology, insurance coverage, and a perceived lack of medical evidence for screening . The most significant barrier to skin cancer screening for SOTR reported was the perceived lack of medical evidence for skin cancer screening among transplant providers.…”
Section: Introductionmentioning
confidence: 99%